1966
DOI: 10.1126/science.154.3752.1019
|View full text |Cite
|
Sign up to set email alerts
|

Phytohemagglutinin: Inhibition of the Agglutinating Activity by N -Acetyl-D-Galactosamine

Abstract: The effect of simple sugars on the agglutinating activity of phytohemagglutinin was studied. N-Acetyl-d-galactosamine selectively inhibits the agglutination of leukocytes and erythro- cytes by phytohemagglutinin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…Also, much information has been accumulated on their nature and mode of action on animal cells (3,4,6,7,16,19). However, their role in the plant is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, much information has been accumulated on their nature and mode of action on animal cells (3,4,6,7,16,19). However, their role in the plant is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that many plants contain phytohemagglutinins or lectins (3,4,6,18). Also, much information has been accumulated on their nature and mode of action on animal cells (3,4,6,7,16,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BHA agglutinated also the erythrocytes from various animals, including rats, rabbits, dogs, mice and sheep. The titer of agglutination of papain or neuraminidase treated cells was always much higher than that obtained for untreated cells, resembling the behaviour of "incomplete" antibodies and certain phytohemagglutinins [ 1, 2,8,141 . These results are presented in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these B-cell mitogens, phytohemagglutinin (PHA) and concanavalin A (Con A), well-known mitogens for thymusdependent lymphocytes (T cells), exert adjuvanticity for antibody response to sheep 138 H. ISHIKAWA ET AL erythrocytes (SRBC) in mouse spleen cell cultures under appropriate conditions (8,32,33). Although receptors for PHA and Con A on T cells have been shown to be certain sugar moieties existing on the cell membrane (2,25,37), receptors for the B-cell mitogens on B cells are still obscure, and furthermore, the molecular mechanisms in triggering by these B-cell or T-cell mitogens of lymphocyte activation that leads to stimulation of DNA synthesis and to enhanced antibody response to antigenic stimulation are unknown.…”
mentioning
confidence: 99%